A review of cryptographic impact in cybersecurity on smart grid: threat, challenges and countermeasures - Hasan, Md Mehedi; Mohd Ariffin, Noor Afiza; Mohd Sani, Nor Fazlida (Little Lion Scientific, 2021)
The continuous development of information communication technology assists the traditional electricity grid to become a modern integrated platform. As Internet-of-Thing’s technologies involve in smart grid features together with delivery emerging services utility side to end user via unreliable channel. Due to high dependency of communication system lead catastrophic security vulnerabilities. In addition, loss data security or privacy along hampered core security objectives confidentiality, integrity, availability and broken connection between them. Therefore, significant number of researches worked mitigates those types of threads by the use of cryptographic aspect. It is fascinated to kept data secure and ensures the privacy between two parties during transmission or any kind of data share in distribute manner. In this paper, we present comprehensive survey on cryptographic impact in smart grid for security objectives, requirement, and challenges. Particularly, produces security threats, examined current research work countermeasure technique. We aim to supply deeper understanding about role of cryptographic aspect in smart grid to shed light and guide future research direction for cyber-security protection against from malicious attacker in smart grid application.